The Genetics of Vitamin C Loss in Vertebrates - Drouin, Guy; Godin, Jean-Rémi Godin; Pagé, Benoît (Université d'Ottawa | University of Ottawa, 2011)
Vitamin C (ascorbic acid) plays important roles as an anti-oxidant and in collagen synthesis. These important roles, and the relatively large amounts of vitamin C required daily, likely explain why most vertebrate species are able to synthesize this compound. Surprisingly, many species, such as teleost fishes, anthropoid primates, guinea pigs, as well as some bat and Passeriformes bird species, have lost the capacity to synthesize it. Here, we review the genetic bases behind the repeated losses in the ability to synthesize vitamin C as well as their implications. In all cases so far studied, the inability to synthesize vitamin C is due to mutations in the L-gulono- -lactone oxidase (GLO) gene which codes for the enzyme responsible for catalyzing the last step of vitamin C biosynthesis. The bias for mutations in this particular gene is likely due to the fact that losing it only affects vitamin C production. Whereas the GLO gene mutations in fish, anthropoid primates and guinea pigs are irreversible, some of the GLO pseudogenes found in bat species have been shown to be reactivated during evolution. The same phenomenon is thought to have occurred in some Passeriformes bird species. Interestingly, these GLO gene losses and reactivations are unrelated to the diet of the species involved. This suggests that losing the ability to make vitamin C is a neutral trait.
Keywords: Ascorbic acid; biosynthesis; GLO gene; L-gulono-gamma-lactone oxidase; pseudogene; vitamin C